High‐rate and dendrite‐free liquid alloy anode for high energy potassium metal batteries. Issue 5 (21st March 2022) - Luo, Tingting; Zhao, Qianqian; Liu, Yiwei; Meng, Weidong; Sun, Qi; Dai, Lei; Liu, Shan; Wang, Ling
Abstract: Potassium ion batteries are considered as promising candidates for electrochemical energy storage device due to its low‐cost and high theoretical capacity. However, it is seriously limited by the dendrite growth. Liquid Na‐K alloy has excellent kinetic mass transfer characteristics which could avoid dendrite fundamentally. However, due to its large surface tension, liquid alloy is difficult to be processed and used in practical applications. Herein, a flexible and processable graphene‐based liquid alloy anode (Na‐K@rGO) was designed. Thanks to the reasonable porous structure, good chemical and mechanical stability and rapid charge transfer of graphene matrix, Na‐K@rGO anode exhibits excellent cycle stability and rate performance. The batteries could cycle stably and exhibit dendrites‐free property. Our work offers a simple approach to construct dendrite‐free anodes for high energy density and long‐lifespan potassium metal batteries. Abstract : In this work, a flexible and processable graphene‐based liquid alloy anode was designed. Thanks to the reasonable porous structure, good chemical/mechanical stability and rapid charge transfer of graphene matrix, the Na‐K@rGO anode exhibits an excellent cycle stability and rate performance.